Prehabilitation during neoadjuvant therapy in patients with cancer of the upper gastrointestinal tract and rectum—the study protocol - Chmelova, Irina; Pastucha, Dalibor; Hudecek, Tomas; Guran, Zdenek; Ciecotkova, Sona; Martínek, Lubomír; Zubikova, Jana; Matlova, Alena; Dolezel, Jakub; Salounova, Dana; Chmelo, Jakub (Frontiers in Sports and Active Living, 2025)
AimsThe concept of prehabilitation, defined as interventions aimed at enhancing a patient's functional capacity prior to an impending physiological stressor, may contribute to reduced postoperative morbidity and mortality. The study's goal is to verify or refute the feasibility of a prehabilitation programme for two diagnostic patient groups during neoadjuvant chemo(radio)therapy, which is prescribed before the scheduled surgical procedure. This is a single group study design, with all patients enrolled receiving the intervention.MethodsThis is an interventional feasibility study of a prehabilitation programme in the form of physical training conducted at home. The training consists of progressively dosed walking and strength exercises for selected muscle groups. Data will be monitored telemetrically and also through telephone contact with participants. Primary outcomes include: the percentage of patients interested in participating in the study out of all patients indicated for neoadjuvant therapy at University Hospital Ostrava during the observed period, the percentage of patients who complete the prehabilitation programme until the date of surgery and individual patient compliance. Secondary outcomes include physical fitness parameters obtained from cardiopulmonary exercise testing, grip strength measured by a dynamometer, changes in body composition, EORTC QLQ-C30 quality of life questionnaire, and a questionnaire on the subjective perception of the exercise programme. Both primary and secondary outcomes will be compared between study arms (two diagnostic groups). The study is registered at ClinicalTrials.gov, ID: NCT05646043.ConclusionThe results of this study can serve as a foundation for larger, multicentre, controlled studies in the future.